Financial Performance and Financial Distress Assessment of PT Krakatau Steel (Persero) Tbk (2020–2024) - Muhammad Avicenna Rabama; Eneng Nur Hasanah (LPPM Politeknik Pratama, 2026)
The financial performance and financial distress status of PT Krakatau Steel (Persero) Tbk with stock code KRAS will be evaluated in this research for a five-year period during 2020 to 2024. Although KRAS experienced a temporary financial recovery in 2020 following debt structuring, they continued not to make money and raise concerns over their financial sustainability. The financial performance analysis of KRAS will be conducted in this research. The research adopts a case study methodology using a quantitative technique with secondary data obtained from financial statements where financial performance is measured using financial ratios with a focus on profitability, liquidity, solvency, and activity, with DuPont analysis used in combination with Return on Equity analysis. Financial distress is measured using a total of three major Financial Distress models: Altman Z-Score, Ohlson O-Score, and Zmijewski X-Score with comparisons based on ASEAN Steel firms. The results show a serious problem in profit margins, with Net Profit Margin, Return on Assets, and Return on Equity becoming negative in 2023-2024 because of increasing production costs, reduced pricing power, weak efficiency, and high leverage levels. Liquidity remains a persistent problem, although leverage positions appear to be high because of financial distress. The DuPont analysis shows that profit margins is declining from Return on Equity, which is worsened by high leverage positions. All three distress models classify KRAS as distressed during all years, which shows increasing distress in the last two years. The practical significance of this study lies in the fact that it’s empirical data of how financial performance analysis and financial distress analysis can be integrated and used in state-owned companies in capital-intensive sectors. The results can be used as a source of evidence-based insight into which managers and policymakers can rely on when designing a strategy for such companies.